The combined negative effect of temperature, UV radiation and salinity on eDNA detection: A global meta-analysis on aquatic ecosystems - Eftychia Tzafesta; Milad Shokri (Ecological Indicators)
Anthropogenic changes in global aquatic biodiversity necessitate the urgent adoption of more efficient biomonitoring approaches. Environmental DNA (eDNA) metabarcoding has emerged as a powerful tool that has enhanced the field of biomonitoring. However, the efficiency of eDNA detection can be hindered by various environmental and methodological factors. This is an area of active research that has not yet been fully crystallized, especially on a large scale where variations in environmental factors might unmask further intricacies. Here, we aimed to investigate the impact of key environmental factors across broad biogeographical areas on eDNA detection and explore how methodological variations in eDNA-based biomonitoring might influence detection outcomes —through a synthesis study conducted under real-world conditions. To address this, we performed a literature search and compiled a dataset from 22 studies of species occurrence from both eDNA and traditional approaches. We examined the effects of temperature, UV, salinity, filter pore size, and DNA fragment length on eDNA detection probability —defined as the likelihood of detecting species through eDNA relative to the total number of species detected by both approaches. The results revealed that temperature, independently and in combination with UV, consistently reduced eDNA detection, meaning that eDNA detection fell in hotter locations and seasons with more intense UV exposure. Similarly, salinity exerts a slight negative impact, whereas filter pore size and DNA fragment size show no effect. Our findings highlight the intricate spatial–temporal effects of environmental factors on eDNA detection efficacy, emphasizing the need to consider them in the execution of eDNA studies.